Harvey Cushing : a life in surgery - Bliss, Michael (Oxford University Press, 2005)
Harvey Cushing (1869-1939) was the founder of brain surgery, an enormous surgical advance. Working at Johns Hopkins Hospital in the early years of the twentieth century, Cushing developed the techniques that enabled surgeons to open the skull, expose the brain, and attack tumors, with a high probability of helping rather than harming patients. Cushing became world famous as the first neurosurgeon, and was one of the first American medical leaders to attract visitors and students from abroad. Moving to Harvard and the Peter Bent Brigham Hospital, Cushing in the 1920s made the apparently miraculous in surgery an every-day reality, as he and his team compiled an astonishing record of treating more than two thousand tumors. Cushing's techniques also enabled him to become the world's leading expert in the pituitary gland, and thus one of the pioneers in endocrinology, who has given his name to "Cushing's syndrome" and "Cushing's disease."; In his spare time Cushing wrote elegant medical essays, won a Pulitzer Prize for his massive biography of William Osler, and amassed a great collection of rare medical books, which are now the basis of the Medical Historical Library at his alma mater, Yale. "Harvey Cushing: A Life in Surgery" is the first biography of Cushing to be published in fifty years. Drawing on new collections of intimate personal and family papers, diaries and patient records, Michael Bliss re-creates both Cushing's professional and, for the first time, his personal life in remarkable detail.